2019
DOI: 10.1165/rcmb.2018-0158oc
|View full text |Cite
|
Sign up to set email alerts
|

Pendrin Mediates Bicarbonate Secretion and Enhances Cystic Fibrosis Transmembrane Conductance Regulator Function in Airway Surface Epithelia

Abstract: Bicarbonate facilitates mucin unpacking and bacterial killing however its transport mechanisms in the airways are not well understood. cAMP stimulates anion efflux through the CFTR (ABCC7) anion channel and this is defective in CF. The anion exchanger pendrin (SLC26A4) also mediates HCO3− efflux and is upregulated by proinflammatory cytokines. Here we examined pendrin and CFTR expression and their contributions to HCO3− secretion by human nasal and bronchial epithelia. In native tissue, both proteins were most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 49 publications
9
51
1
Order By: Relevance
“…6c,d). These data along with previous studies suggest that pendrin-dependent HCO 3 − secretion may be more important in controlling ASL pH [11,27,50]. We are confident that our intrabronchial microelectrode measurements were correct, as the standard curve obtained with this electrode provided reliable and reproducible pH readings (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…6c,d). These data along with previous studies suggest that pendrin-dependent HCO 3 − secretion may be more important in controlling ASL pH [11,27,50]. We are confident that our intrabronchial microelectrode measurements were correct, as the standard curve obtained with this electrode provided reliable and reproducible pH readings (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…An interesting intersect with the concept of properly balancing pendrin function relates to our finding of pendrin downregulation in CF epithelia. This observation differs from a recent publication which instead reported an upregulation of pendrin 36 . The discrepancy could arise from differences in culture conditions, but might also arise from tissue donor differences.…”
Section: Discussioncontrasting
confidence: 99%
“…siRNA knockdown of pendrin mRNA or inhibition of pendrin activity with niflumic acid blocked this interleukin‐stimulated increase in CFTR current. These observations suggested functional coupling between pendrin and CFTR; this coupling has also been suggested by another recent publication 36 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…CFTR interacts with pendrin, and the R region of CFTR is phosphorylated by PKA to bind to pendrin's STAS (sulfate transporter and anti-sigma factor antagonist domain), which activates pendrin [36][37][38]. A recent study showed that pendrin mediates bicarbonate secretion and enhances CFTR function in airway surface epithelia [39]. Whether pendrin is synergistic with CFTR transport of GSH is still unclear.…”
Section: Abnormalities In Cftr/pendrin Transport and Redox Products Omentioning
confidence: 99%